(untitled) (Stamford Journal of Microbiology, 2022)
Suya is a street-hawked food that offers a source of the nourishing menu for its consumers. In this study, the quality and safety of street hawked ready-to-eat suya in Dutse urban was assessed. Twenty skewers of suya were sampled from four sampling points (Hakimi Street, Yelwawa, Takuradua and Mobile base) where it is mostly sold. At each sampling point, five skewers of suya were obtained randomly from the suya vendors in sterile containers that were labeled A to T. Samples were immediately taken to the laboratory where standard methods were employed for the bacteriological assay. The total viable count (TVC) showed that the sample G (1.96 × 107 CFU/g) collected from Yelwawa had the highest load while sample P (8.60 × 106 CFU/g) collected from Takuradua recorded the lowest. Bacillus spp., Staphylococcus spp., Escherichia coli and Streptococcus spp. were detected in the samples. Across the sampling points, percentage of occurrence of bacteria isolated was highest for Escherichia coli (40%) and least for Bacillus spp. (10%). It can be concluded that all the sampled suya assayed in this study recorded bacteriological contaminants. Some of the bacteria isolated in the suya samples can potentially constitute a public health issue as their presence can cause food poisoning and food-borne diseases. Therefore, it is recommended that the producers of street vended suya should follow proper food safety measures during preparation to improve the food quality as well as to reduce imminent public health crisis upon its consumption. Stamford Journal of Microbiology, Vol.12 (1) 2022: 25-30